PECULIARITIES OF UZBEK POETRY IN THE PERIOD OF INDEPENDENCE - Khamdamov, Ulugbek Abdu vahobovich; Hakimjonova, Rano Olimjon kizi (International Journal of Psychosocial Rehabilitation, 2020)
his article explores several peculiarities of Uzbek poetry during the independence period. In particular, poetry is categorized according to the content and method of expression. It also examines the comparative aspects of classical, jaded, Soviet and Soviet poetry, created at different historical stages.